2014
DOI: 10.1177/1936724414526718
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Caregiver Perceptions of Water Intake Recommendations for Young Children and Their Current Beverage Feeding Practices

Abstract: Hispanic children in the United States are at high risk of obesity. Sugar-sweetened beverage consumption (SSB) is a modifiable contributor to obesity. Hispanic children are more likely to drink SSB than non-Hispanic white children. The main goal of the study was to explore caregiver beverage feeding behaviors and evaluate reactions to water intake recommendations for children birth to five years old in a diverse U.S. Hispanic urban community. Findings will be used to develop community-and population-specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Feeding practices and beliefs are defined as food choices and control over food intake made by the mother. Research examining the relationship between fruit and vegetable consumption and BMI reported conflicting findings (Davis, Whaley, & Goran, ; Mason, Welch, & Morales, ) and six studies were inconclusive. History of breastfeeding was assessed in one study and was inversely related to childhood obesity (Davis et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding practices and beliefs are defined as food choices and control over food intake made by the mother. Research examining the relationship between fruit and vegetable consumption and BMI reported conflicting findings (Davis, Whaley, & Goran, ; Mason, Welch, & Morales, ) and six studies were inconclusive. History of breastfeeding was assessed in one study and was inversely related to childhood obesity (Davis et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Nutrition and feeding-related factors = purchasing, preparing unhealthy food, using food as a reward, asking children to finish the food on their plate were reported by parents of obese children Lack of physical activity was not recognized as a risk Kalinowski et al (2012) 91 mother-child dyads of children between 3 and 5 years of age (50% Hispanic) Maternal feeding practices Three themes were recognized: parents had negative memories of being fed in childhood, maternal emotional investment in the child enjoying the meal, & attributing obesity in other people's children to inept or neglectful parenting Lindsay et al (2012) 31 Latina mothers for focus groups, 20 Latina mothers for in-depth interviews Maternal feeding practices Contextualized understanding of factors in mothers' lives that influence child feeding styles and behavior A sense of the prevalence and type of specific barriers for mothers in this population Lowenstein et al (2013) Three focus groups with a total of 24 Hispanic fathers Fathers' perceptions and experiences communicating with their children's provider during clinic visits regarding weight, diet, and physical activity Fathers were involved in their children's health care and found providers to be helpful partners in keeping their children healthy, yet they generally felt "left out" during clinic appointments The quality of the relationship with their children's provider influenced how receptive fathers were to discussing their children's weight, diet, and physical activity behaviors Mason et al (2015) 35 Hispanic caregivers of children aged 0-5 years living in a low-income, predominantly Hispanic community in Chicago, Illinois Maternal feeding practices Increased SSBs and caregivers choose beverages based on cost, availability, health, and behavioral concerns Puerto Rican and Mexican-American participants differed in the range of beverages provided, concerns regarding water intake, and beverage alteration and feeding practices Caregivers universally believe the recommended water intake amount of four-six-ounce servings daily for children is too high Pesch, Harrell, Kaciroti, Rosenblum, and Lumeng (2011) 133 Mothers of preschool-age children, Hispanic Maternal feeding practices More than half (60%) of children of mothers in the Conflicted Control cluster were obese Maternal styles of talking about feeding are associated with maternal and child characteristics Small et al (2009) 11 Mexican mothers of preschoolers Maternal feeding practices Readily associated overweight/obesity with poor mental and physical health Uncertain how they would "know" if their children were overweight status. Food insecurity was defined as, "the lack of access to enough food for an active healthy life that results from the limited or uncertain access to nutritionally adequate and safe foods in socially acceptable ways" (Metallinos-Katsaras, Gorman, Wilde, & Kallio, 2011, p. 627).…”
Section: Author(s)/yearmentioning
confidence: 99%
“…The ‘Influences on Beverage Selection’ theme is about the contexts and maternal strategies that affect beverage purchasing and the control of the child’s behavior by the mother or the child. These include the use of sugar-sweetened beverages as treats, the avoidance of situations such as supermarkets in which clashes between the mother’s and child’s purchase wishes might occur (‘pester power’) [ 50 , 51 , 52 , 53 , 54 , 55 ], and the provision of beverages such as sugar-sweetened beverages so mothers could avoid their tantrums (also reported in previous work [ 21 , 22 ]). This is similar to Weston’s [ 24 ] findings that satisfying the child’s demands and appetite were major considerations for mothers.…”
Section: Discussionmentioning
confidence: 84%
“…Some of the perceptual categories shown in Table 2 have been reported before. These include the various health-related constructs like hyperactivity, nutrition, satiety, digestion, dental health [ 16 , 21 , 22 ]; the mainly negative views of sugar and sugary beverages [ 16 , 17 , 20 , 22 , 48 ]; the benefits of milk [ 49 ], particularly for breakfast and at bedtime [ 21 ]; the concrete attributes of packaging such as lids to prevent spillage [ 19 , 22 ]; and the fear of additives [ 16 , 19 ]. The most novel feature of this study is the sheer diversity of the perceptions held by this small group of mothers and the complexity of the combinations of perceptions (‘constructs’) held by individual mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation